Parathyroid Carcinoma in Patients that Have Undergone Surgery for Primary Hyperparathyroidism - Libánský, Petr; Adámek, Svatopluk; Broulík, Petr; Fialová, Martina; Kubinyi, Josef; Lischke, Robert; Naňka, Ondřej; Pafko, Pavel; Šedý, Jiří; Bobek, Vladimír (In vivo (Athens, Greece), 2017)
BACKGROUND/AIM: Parathyroid carcinoma is a rare clinical entity, which represents one of the main reasons, why surgery should be performed in specialized centres. Preoperatively, it is very difficult to distinguish between benign and malignant hyperparathyroidism. PATIENTS AND METHODS: During the years 1996-2016, we performed 2,220 operations in 2,075 patients with a diagnosis of primary hyperparathyroidism. RESULTS: Among these 2,220 operations, there were 16 operations for parathyroid carcinoma. These 16 operations, including reoperations, were performed in four patients. Two patients had no reoperation, but another 2 patients required 14 reoperations in total. Parathyroid carcinoma was described in 0.2% of all patients with a diagnosis of primary hyperparathyroidism. The number of operations was 0.73% of all operations of primary hyperparathyroidism in years 1996-2016. CONCLUSION: Prognosis of parathyroid carcinoma is quite favourable, patients evidence a long-term survival rate after the primary operation. However, every reoperation increases the number of possible complications, including recurrent laryngeal nerve injury.
Keywords: surgery; paratyreoidektomie; Humans; lidé středního věku; Parathyroid carcinoma; Symptom Assessment; Female; Aged; nádory příštítného tělíska; Parathyroid Neoplasms; výsledek terapie; senioři; lidé; Biomarkers; multimodální zobrazování; určení symptomu; Postoperative Complications; pooperační komplikace; biologické markery; ženské pohlaví; Parathyroidectomy; Male; Middle Aged; Treatment Outcome; primární hyperparatyreóza; hyperparathyroidism; Hyperparathyroidism, Primary; mužské pohlaví; Multimodal Imaging